Evaluasi Struktur Bangunan Pasar Inpress Blok IV Gedung B dengan Metode Pushover - Lisyana Junelin Restu; Eka Juliafad; Fajri Yusmar (CIVED, 2021)
AbstractInpres market block IV Pasar Raya Padang is not designed as a shelter building, but is designated as a vertical evacuation site when a tsunami occurs. This study aims to evaluate the structural performance of Inpress market block IV zone B. The method used for this research is the pushover analysis method. According to FEMA P-646/2019, vertical evacuation refuge structures are included in tsunami risk category IV, based on the risk category the maximum performance level is at the Immediate Occupancy (IO). For loads on buildings, refer to SNI 1727:2020 and SNI 1726:2019 for earthquake loads. For the calculation of the capacity of concrete structural elements, refer to SNI 2847:2019. Structural analysis was carried out using the SAP2000 version 16. After analysis, based on performance points, drift ratio that occur due to earthquake loading in X-direction and Y-direction are 0,05875% and 0,0067%. The maximum total drift that occurs is smaller than that required by ATC-40 for the Immediate Occupancy performance level, which is 1%. Thus, the structure performance level is Immediate Occupancy. This means that the Inpress market block IV building is still strong enough against earthquake loads.